Fracture Risk and Health Profiles Differ According to Relationship Status: Findings from the Hertfordshire Cohort Study - Westbury, LD; Pearse, C; Bevilacqua, G; Fuggle, NR; Ward, KA; Cooper, C; Dennison, EM (Springer, 2024)
Registry studies have suggested associations between relationship status and fracture risk. We considered associations between relationship status and incident fracture in the Hertfordshire Cohort Study, comprising community-dwelling older adults, and explored associations between socioeconomic and lifestyle factors with relationship status. 2997 participants completed a baseline questionnaire (1998–2004) and clinic visit. Participants were followed up until December 2018 using Hospital Episode Statistics, which report clinical outcomes using codes from the 10th revision of the International Classification of Diseases (ICD-10); these codes were used to ascertain incident fractures. Relationship status (not currently married/cohabiting vs currently married/cohabiting) at baseline was examined in relation to incident fracture using Cox regression. Associations between baseline characteristics and relationship status were examined using logistic regression. Mean baseline age was 66.2 years. 80% were married/cohabiting at baseline; 15% had an incident fracture (mean (SD) follow-up duration: 14.4 (4.5) years). The following were related to greater likelihood of not being married/cohabiting: older age (women only); higher BMI (women only); current smoking; high alcohol consumption (men only); poorer diet quality (men only); lower physical activity; leaving school before age 15 (women only); and not owning one’s home. Those not married/cohabiting had greater risk of incident fracture compared to those who were (age-adjusted hazard ratios (95% CI) 1.58 (1.06, 2.38) among men, 1.35 (1.06, 1.72) among women); associations were attenuated after accounting for the above factors associated with relationship status in the corresponding sex. This suggests that differences in health profiles and lifestyle according to relationship status may explain the association between relationship status and fracture risk.